If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m + m + 6 + (m + 6) * 3 = 89 Reorder the terms: m + m + 6 + (6 + m) * 3 = 89 Reorder the terms for easier multiplication: m + m + 6 + 3(6 + m) = 89 m + m + 6 + (6 * 3 + m * 3) = 89 m + m + 6 + (18 + 3m) = 89 Reorder the terms: 6 + 18 + m + m + 3m = 89 Combine like terms: 6 + 18 = 24 24 + m + m + 3m = 89 Combine like terms: m + m = 2m 24 + 2m + 3m = 89 Combine like terms: 2m + 3m = 5m 24 + 5m = 89 Solving 24 + 5m = 89 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + 5m = 89 + -24 Combine like terms: 24 + -24 = 0 0 + 5m = 89 + -24 5m = 89 + -24 Combine like terms: 89 + -24 = 65 5m = 65 Divide each side by '5'. m = 13 Simplifying m = 13
| 2+3x+5x=18+5 | | 3e-6=-2e-4-7 | | 9k^2-12-1=0 | | 2+3x+5=18+5 | | f(x)=3x^2-6x+2 | | -11.2+8.4+4q=-0.08 | | 6a+8=-2a+8 | | 390-60x=578-100x | | 23-14=3(x-1) | | .87x=.5x+.75x | | 1/8*8/37= | | 2/3x-3/2x-1=5/6 | | 500=200(1+x) | | 500=200(1+x)5 | | 3/8x-50 | | 2-20/5x3 | | -(5x-11)+4(5x+7)= | | 6x^2-12=-2x | | 5x^2/x^3-x^3 | | 3z+2(-5z)+6= | | (3m-4)(2m+5)=0 | | 4+ln(x+3)=3 | | 8z-0.6=9z | | 5y-6=6y-1 | | -5j+(-2)+3= | | y--9=3/4(x-5) | | 2z+6=4z-3 | | =2u^10v^9w^8*w*9v^2*4u^9 | | (2m^2*n^-2*p^0/m^-2)^3= | | x^2*x^9= | | 0.3(0.2x-1)=0.4(0.5x-1) | | 2/5-7/20x=2 |